RESORT HOTEL DENGAN PENDEKATAN ARSITEKTUR REGIONALISME DI KAWASAN WISATA MANDEH, SUMATERA BARAT - Ryandhika Ruddy Farel; Widi Suroto; Ana Hardiana (ARSITEKTURA, 2017)
Resor Hotel becomes the most important and unseparated part of tourism. Every region which has its own tourism destination is usually supported by good accommodation, one of it is resor hotel, it can be seen from popular tourism destination in Indonesia, such as Bali or Lombok,besides having beautiful beach panorama, both islands are also have many Resor Hotel with unique concept and design,  which becomes the main attraction for tourist. Besides Bali and Lombok actually there is a lot of coastal tourism potentials owned by another regional areas in Indonesia, but not exposed yet, one of them in West Sumatera. In West Sumatra, there is a new tourist area named Mandeh Tourim Area, this area is located in the south coast of West Sumatera, and located next to the Indian Ocean, although it has beautiful natural panorama, the accomodation in this area is still incomplete, one of it is the Resor Hotel that good enough to accommodate activiteies there, based on that phenomenon the urgent problem is how to plan Resor Hotel concept that can accommodate the number of visitors coming to Mandeh Tourim Area, and also feature characteristic of West Sumatra culture, as promotion of West Sumatera culture out. Regionalism Architecture used as design approaches in a way to show off West Sumatera culture to tourist that come by, thus this Resor Hotel can give tourist a new vision and knowledge about West Sumatera culture, this culture usually shown in building shape that have unique character, such as shape of the roof, carving wall, and building material, these character will applied in Resor Hotel design Key Word : Mandeh Tourism Area , Regianlism Architecture,  Resort Hotel